Analisis Framing Berita Kecelakaan KM Sinar Bangun di Surat Kabar Harian Analisa - L. Tobing, Yogo Pamungkas (Communication & Social Media, 2023)
The purpose of this article is to analyze the framing of the Motorboat (KM) Sinar Bangun accident news in the daily newspaper Analisa. The research objective is to understand how Analisa daily frames the Motorboat (KM) Sinar Bangun accident news. The theory used to delve into this research is the Mass Media Social Construction Theory, Framing Analysis, News, and Shoemaker and Reese's Theory. The research subject consists of six news articles in the Analisa daily newspaper from June 20, 2018, to July 4, 2018. The method used in this research is a qualitative method with a constructivist paradigm. The analysis technique employed is the framing analysis model by Zhongdang Pan and Gerald M. Kosicki. The results of the research indicate that Analisa daily frames the Motorboat (KM) Sinar Bangun accident news as information that must be known by the community in the city of Medan. This research also shows that the government and the ship management should conduct a serious evaluation to prevent similar incidents in the future.